Oden Arctic Technology Research Cruise (OATRC 2015) - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during 18 September to 1 October 2015 - Oden Arctic Technology Research Cruise (OATRC 2015) - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during 18 September to 1 October 2015. - Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2017)
In September 2015, the research expedition Oden Arctic Technology Research Cruise (OATRC 2015) was carried out in the Arctic Ocean north of Svalbard with the Swedish icebreakers Oden and Frej.

The expedition was carried out by the Norwegian University of Science and Technology (NTNU) in collaboration with the Swedish Polar Research Secretariat. Two similar expeditions was carried out in 2012 and 2013.

OATRC 2015 was a project associated with Sustainable Arctic Marine and Coastal Technology (SAMCoT), which is a centre for research-based innovation, initiated by the Research Council of Norway and hosted by NTNU.

The main scientific scope of the research expedition was:
Collection of full-scale data necessary to build, calibrate and validate models for floaters in ice.
Collection of full-scale data necessary to build, calibrate and validate models for Ice Management operations.
Collection of data relevant for health, safety and environmental research.

Investigation of exposure to whole body vibration for icebreaker crew.

Whole body vibration denotes that the entire body is exposed to vibrations. Studies show that the risk for pain in the lower back is doubled when people are exposed to whole body vibrations.

Few investigations have been conducted regarding exposure to whole body vibration for icebreaker crews. Previous studies have focused on other types of vessels, not icebreakers. The main purpose of the study was to measure level of exposure to whole body vibrations for icebreaker crew during Arctic icebreaking conditions. The levels of exposure will be compared to levels of acceptance as published by the Swedish Work Environment Authority and international standards.

Depending on the results of the measurements, researchers may also investigate whether problems with the lower back are more common among icebreaker crews.

The project was a test of the ability to use an ice radar to make continuous measurements of sea ice thickness from the icebreaker Oden. Different antenna types and different frequency ranges was tested and the software was adapted for use on a ship. An intermediate goal was to be able to read the measurements in real-time. The radar system has previously been used for snow and ice measurements in Antarctica and in Swedish fells.
The researchers used CTD (Conductivity, Temperature, Depth), an oceanography instrument used to determine the salinity, temperature, and depth of the ocean, to quantify the water masses in a transect going from the shallow shelf out into deeper waters and through the ice front.

Water samples was also collected to answer these questions:

Can the differences in phytoplankton and bacterial communities found in a transect towards the ice front be explained by changes in physical/hydrographical factors?
Does the ice and its microflora , direct or indirect, influence the plankton communities through shading or seeding the water with organisms and organic matter?

The data will add to other chemical, biological, and physical data to give a better understanding of the biological functions at the ice edges, which are important for understanding of production, biodiversity and carbon circulation in Arctic waters.

The researchers retrieved SAR data from Sentinel-1 and a number of other satellites during the expedition. The images was processed in near-real-time to create products of ice drift and ice convergence/divergence.

This data set contains meteorological, oceanographic and ship data collected during the expedition Oden Arctic Technology Research Cruise 2015 (OATRC 2015), which was an international research cruise using the icebreaker Oden in the Arctic Ocean.

Data includes meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Cloud height/cloudiness, Photosynthetic Active Radiation (PAR).

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Further metadata on instrumentation and the individual variables can be found in the info file. Graphics and files describing the route are included in the package.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.

I september 2015 genomfördes den norsk-svenska forskningsexpeditionen Oden Arctic Technology Research Cruise (OATRC 2015) med de svenska isbrytarna Oden och Frej i Arktiska oceanen norr om Svalbard.

Expeditionen var ett samarbete mellan Norges teknisk-naturvitenskapelige universitet i Trondheim (NTNU) och Polarforskningssekretariatet. Två liknande expeditioner genomfördes 2012 och 2013.

OATRC 2015 var ett projekt inom Sustainable Arctic Marine and Coastal Technology (SAMCoT), som är ett center för forskningsbaserad innovation som inrättats av Norges forskningsråd med NTNU som värd.

Ombord på isbrytarna undersökte den norska forskargruppen bland annat havsisens och isbergens fysikaliska och mekaniska egenskaper och studerade isbrytarna Oden och Frejs prestanda och framkomlighet under skiftande isförhållanden.

Det utfördes en studie av isbrytarbesättningens exponering för helkroppsvibrationer. Helkroppsvibration innebär att hela kroppen utsätts för vibrationer, antingen när någon står, sitter eller ligger. Exponering för helkroppsvibrationer påverkar framförallt nedre delen av ryggen och studier visar att risken att drabbas av ryggsmärtor dubbleras när man utsätts för helkroppsvibrationer. Det finns få tidigare studier av exponering för helkroppsvibrationer på isbrytare. Huvudsyftet med den här studien var att mäta exponeringsnivåerna som en isbrytarbesättning utsätts för under arktiska isbrytningsförhållanden. Exponeringsnivåerna kommer att jämföras med de värden som anges i Arbetsmiljöverkets föreskrifter och internationella standarder. Beroende på resultatet av mätningarna kan det också bli aktuellt att närmare undersöka om problem med nedre delen av ryggen är vanligt bland besättningen.

Under expeditionen ingick också en test av möjligheten att använda en isradar för att göra kontinuerliga mätningar av havsisens tjocklek under gång. Olika antenntyper och olika frekvensomfång testades och mjukvaran anpassades för bruk från ett fartyg. Ett delmål var även att mätningarna i framtiden ska kunna avläsas i realtid. Radarsystemet har tidigare använts för snö- och isdjupsmätningar i Antarktis och i svenska fjällen.

CTD (en förkortning för Conductivity, Temperature, Depth) användes under expeditionen. CTD är ett instrument som används inom havsforskningen för att mäta salthalt, temperatur och djup. Med hjälp av CTD arbetade forskarna under expeditionen med att kvantifiera vattenmassorna i transekter som sträckte sig från grundhav, genom iskanten och ut på djupare vatten.

Vattenprover samlades även in för att besvara frågorna:

Kan skillnader i växtplankton- och bakteriesamhällen vid iskanten förklaras av förändringar i fysiska och hydrografiska faktorer?
Har isen och dess mikroflora, direkt eller indirekt, påverkan på planktonsamhällen genom skuggning eller ympning av vattnet med organismer och organiskt material?

Insamlad data kombineras med andra kemiska, biologiska och fysiska data för att ge mer kunskap om de biologiska funktionerna vid iskanten, vilka är viktiga för att förstå produktion, biologisk mångfald och koldioxidcirkulation i Arktiska oceanen.

Forskarna hämtade SAR-data från Sentinel-1 och ett antal andra satelliter under expeditionen. Materialet behandlades i nära realtid för att ge en bild av isens rörelser för att underlätta isövervakning

This data set contains meteorological, oceanographic and ship data collected during the expedition Oden Arctic Technology Research Cruise 2015 (OATRC 2015), which was an international research cruise using the icebreaker Oden in the Arctic Ocean.

Data includes meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Cloud height/cloudiness, Photosynthetic Active Radiation (PAR).

Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Water depth.

Further metadata on instrumentation and the individual variables can be found in the info file. Graphics and files describing the route are included in the package.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.
Oden Arctic Technology Research Cruise (OATRC 2015) - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden från 18 september till 1 oktober 2015 - Oden Arctic Technology Research Cruise (OATRC 2015) - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during 18 September to 1 October 2015.
Keywords: back pain; ryggont; industrial injuries; arbetsskador; Meteorology; Meteorologi; ATMOSPHERE; ATMOSPHERIC WINDS; ATMOSPHERIC TEMPERATURE; AIR TEMPERATURE; ATMOSPHERIC WATER VAPOR; HUMIDITY; CLOUDS; ATMOSPHERIC PRESSURE; SURFACE PRESSURE; OCEANS; SALINITY; DENSITY; PHOTOSYNTHETICALLY ACTIVE RADIATION; OCEAN TEMPERATURE; WATER TEMPERATURE; WATER DEPTH; SEAFLOOR TOPOGRAPHY; BATHYMETRY; SURFACE WINDS; BIOSPHERE; VEGETATION; CONDUCTIVITY; The icebreaker Oden; Isbrytaren Oden; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Engineering and Technology; Teknik; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Environment; Miljö